2016
DOI: 10.1364/boe.7.002373
|View full text |Cite
|
Sign up to set email alerts
|

Angle correction for small animal tumor imaging with spatial frequency domain imaging (SFDI)

Abstract: Spatial frequency domain imaging (SFDI) is a widefield imaging technique that allows for the quantitative extraction of tissue optical properties. SFDI is currently being explored for small animal tumor imaging, but severe imaging artifacts occur for highly curved surfaces (e.g. the tumor edge). We propose a modified Lambertian angle correction, adapted from the Minnaert correction method for satellite imagery, to account for tissue surface angles up to 75°. The method was tested in a hemisphere phantom study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…Because the single snapshot collects phase information as well, there is no additional acquisition time necessary to measure the sample's phase, though calibration steps are added to create distance-dependent correction factors. Profilometry corrections are therefore necessary for quantitative imaging of samples with variations in height and also help reduce imaging artifacts [16,17]. These previous studies have also demonstrated an upper limit of 75° for correcting the reflection angle of the sample surface, though further validation is needed for this endoscopic implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the single snapshot collects phase information as well, there is no additional acquisition time necessary to measure the sample's phase, though calibration steps are added to create distance-dependent correction factors. Profilometry corrections are therefore necessary for quantitative imaging of samples with variations in height and also help reduce imaging artifacts [16,17]. These previous studies have also demonstrated an upper limit of 75° for correcting the reflection angle of the sample surface, though further validation is needed for this endoscopic implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Profile corrections are absolutely crucial for both SFDI [16,17] and SSOP [20] as varying sample height causes uncorrected measurements of absorption and reduced scattering properties. Hence, this work also implements and demonstrates the need for a height-based correction.…”
Section: Endoscopic Ssopmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging of the breast specimen demonstrated co-localization of scattering information with a volumetric micro-CT scan. Imaging irregular specimen surfaces may pose a challenge in the future studies aimed at whole specimen imaging; however, if flattening the tissue surface with the custom acrylic holder does not suffice, a recently published modified Lambertian model has shown to effectively mitigate surface curative artifacts in spatial frequency domain imaging applications (Zhao et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The basic setup of the camera and projector is shown in Figure 1, where imaging is done in an inverted geometry through a glass slide in order to mitigate surface curvature artifacts of the sample, arising when the sample is non-normal to the optical axis. Although these artifacts pose a challenge for in-vivo translation, recent work aims to mitigate their affects [15]. The digital micromirror based projection device is coupled to multiple LEDs as light sources.…”
Section: Experimental Methodsmentioning
confidence: 99%